Promotion in the Saudi Civil Service System (International Journal of Financial, Administrative and Economic Sciences, 2026)
Promotion is one of the rights enjoyed by public employees. It is a means of achieving job stability, increasing employee job satisfaction, and, thanks to it, increasing their financial benefits. The study of promotion within the Saudi civil service system aims to highlight the approved standards for promotion, the conditions for promotion and its obstacles, and the control over promotion decisions, which leads to the question: Was promotion, as a method for filling public positions, a means of enhancing the efficiency of government human resources in the Kingdom? This study adopts a descriptive and analytical approach by examining and analyzing the legal provisions related to promotion criteria, conditions, obstacles, and control. It will also adopt a critical approach by highlighting shortcomings. The study showed that the criteria adopted for promotion are seniority, competence, and the dual criterion that combines the two. There are also some conditions for promotion, such as vacancy the position to which one wishes to be promoted, and the issuance of a promotion decision. However, in some cases, there are obstacles to promotion, such as secondment, study leave, exceptional leave, and disciplinary trial. In all cases, promotion decisions are subject to dual oversight: administrative and judicial. This study concluded that the legislator must take into account performance evaluation for at least the last three years prior to promotion, and not just the most recent year's evaluation. It is also concluded that the employee should be placed on a one-year probationary period after receiving a promotion to determine his suitability for the new position.
Keywords: Public Employee; Promotion Criteria; Promotion Conditions; Promotion Obstacles; Supervision of Promotion Decisions